The Effect of Serotonin-Targeting Antidepressants on Neurogenesis and Neuronal Maturation of the Hippocampus Mediated via 5-HT1A and 5-HT4 Receptors - Segi-Nishida, Eri (Frontiers in Cellular Neuroscience, 2017)
Antidepressant drugs such as selective serotonin reuptake inhibitors (SSRIs) specifically increase serotonin (5-HT) levels in the synaptic cleft and are widely used to treat mood and anxiety disorders. There are 14 established subtypes of 5-HT receptors in rodents, each of which has regionally different expression patterns. Many preclinical studies have suggested that the hippocampus, which contains abundant 5-HT1A and 5-HT4 receptor subtypes in the dentate gyrus (DG), is critically involved in the mechanisms of action of antidepressants. This review article will analyze studies demonstrating regulation of hippocampal functions and hippocampus-dependent behaviors by SSRIs and similar serotonergic agents. Multiple studies indicate that 5-HT1A and 5-HT4 receptor signaling in the DG contributes to SSRI-mediated promotion of neurogenesis and increased neurotrophic factors expression. Chronic SSRI treatment causes functions and phenotypes of mature granule cells (GCs) to revert to immature-like phenotypes defined as a “dematured” state in the DG, and to increase monoamine reactivity at the dentate-to-CA3 synapses, via 5-HT4 receptor signaling. Behavioral studies demonstrate that the 5-HT1A receptors on mature GCs are critical for expression of antidepressant effects in the forced swim test and in novelty suppressed feeding; such studies also note that 5-HT4 receptors mediate neurogenesis-dependent antidepressant activity in, for example, novelty-suppressed feeding. Despite their limitations, the collective results of these studies describe a potential new mechanism of action, in which 5-HT1A and 5-HT4 receptor signaling, either independently or cooperatively, modulates the function of the hippocampal DG at multiple levels, any of which could play a critical role in the antidepressant actions of 5-HT-enhancing drugs.